Liquidity as a Moderator Between Asset Structure, Business Risk, and Capital Structure - Sugiyarti, Listya; Anggraini, Fitria (Universitas Pamulang, 2024)
This research aims to analyze the influence of asset structure and business risk on capital structure with liquidity as a moderating variable. The research method used is quantitative. The type of data used is secondary data. The sampling method used in this study is purposive sampling. The number of samples in this study is 10 companies over a research period of 6 years, resulting in 60 samples of financial report data. Data processing using Eviews 9 with related data. The results of this study indicate that, partially, the Asset Structure has a significant negative effect on the Capital Structure, while Business Risk does not have a significant effect on the Capital Structure. Liquidity cannot moderate the influence of Asset Structure and Business Risk on Capital Structure. The simultaneous testing results indicate that Asset Structure and Business Risk simultaneously affect Capital Structure. Keywords: Asset Structure, Business Risk, Capital Structure, Liquidity